Customer satisfaction towards service quality of public bus transport: a case study at Melaka Central (MC) / Rahil Abu Bakar and Norfarahin Dzulkifli - Abu Bakar, Rahil; Dzulkifli, Norfarahin (Faculty of Administrative Science and Policy Studies, 2013)
This research is about customer satisfaction towards service quality of public bus transport in Melaka Central (MC), Melaka. The objective of this research is to determine the relationship between service quality dimension which are tangibility, reliability, responsiveness, assurance and empathy that influence customer satisfaction. About 200 respondents were selected as sample size of this research. Convenience sampling technique was used when selected the 200 respondents at Melaka Central. The respondents were required to answer questionnaire that consist of 32 questions. The researcher use Descriptive Statistic, Cronbach’s Alpha and Spearman Rank Order Correlation to analyze the data gathered by using Statistical Package for Social Science (SPSS) version 20.0. The result indicates that there are positive correlations between service quality dimension and customer satisfaction.